Minor League Baseball Stadiums and Urban Redevelopment in Mid-Sized American Cities - Dercks, Kory (My University, 2013)
As America's cities continue to grow outward through suburbanization, many cities are looking to economically revitalize their downtowns. One method has involved city o cials and owners of Minor League Baseball teams working together to spur redevelopment by building stadiums downtown with the hope that the stadiums will stimulate economic success with new residenial housing and commercial expansion. The purpose of this research was to investigate the changes within the neighborhoods of a sample of cities with stadiums that opened between 1994 and 2013 through a number of geographic methods.
Color poster with text, images, tables, graphs, photographs, maps, and charts.
Keywords: Minor League Baseball; Urban planning; Downtown revitalization; Posters